About Abortion: Reflection & Response - Pozen, David E.; Sanger, Carol (Columbia Journal of Gender and Law, 2017)
Carol Sanger, About Abortion: Terminating Pregnancy in Twenty-First Century America (2017) The Abortion Closet (with a Note on Rules and Standards) Reflection by David E. Pozen Closets, Standards, Abortion: A Reply to Professor PozenResponse by Carol Sanger